Klotho sensitive regulation of dendritic cell functions by vitamin E. Issue 1 (December 2016) - Xuan, Nguyen; Trang, Phi; Phong, Nguyen; Toan, Nguyen; Trung, Do; Bac, Nguyen; Nguyen, Viet; Hoang, Nguyen; Hai, Nong
Abstract Background Dendritic cells (DCs) are the most potent professional antigen-presenting cells for naive T cells to link innate and acquired immunity. Klotho, an anti-aging protein, participates in the regulation of Ca2+ dependent migration in DCs. Vitamin E (VitE) is an essential antioxidant to protect cells from damage and elicits its inhibitory effects on NF-κB-mediated inflammatory response. However, the roles of VitE on mouse DC functions and the contribution of klotho to those effects both are unknown. The present study explored the effects of VitE on klotho expression, maturation, ROS production and migration in DCs. Methods The mouse bone marrow cells were isolated and cultured with GM-CSF to attain bone marrow-derived DCs (BMDCs). Cells were stimulated with LPS (100 ng/ml) in the presence or absence of VitE (500 µM). RT-PCR and immunoprecipitation methods were employed to determine klotho expression, ELISA to determine cytokine release, flow cytometry to analyze number of CD86+ CD11c+ cells, the intracellular expression of cytokines and reactive oxygen species (ROS) production and a transwell migration assay to trace migration. Results Klotho transcript level and this hormone secretion in DC supernatant were enhanced by VitE treatment and further increased in the presence of NF-κB inhibitor Bay 11-7082 (10 µM). Moreover, VitE treatment inhibited IL-12p70 protein expression of, ROS accumulation in and CCL21-dependent migration of LPS-triggered mature DCs, these effects were reversed followingklotho silencing. Conclusion The up-regulation of klotho by VitE could contribute to the inhibitory effects of VitE on NF-κB-mediated DC functional maturation. The events might contribute to immunotherapeutic effect of VitE on the pathophysiology of klotho-related disease.